ANALISIS NILAI-NILAI PANCASILA PADA TRADISI SEDEKAH SERABI DI DESA TALANG JAWA KABUPATEN EMPAT LAWANG SUMATERA SELATAN - Nofita Sari; Priazki Hajri; Muhammad Ichsan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the low level of understanding among the younger generation regarding the values of Pancasila embedded in the Sedekah Serabi tradition in Talang Jawa Village, Empat Lawang Regency, South Sumatra. Sedekah Serabi is a local cultural tradition that continues to be practiced by the community as an expression of gratitude to Almighty God and as a means of strengthening social relations among community members. This study aims to examine the process of implementing the Sedekah Serabi tradition and to analyze the Pancasila values contained within it. This research employs a qualitative descriptive approach. Data were collected through observation and interviews with traditional leaders, the village head, and members of the Talang Jawa community. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the Sedekah Serabi tradition embodies all five principles of Pancasila, namely Belief in One Almighty God, Just and Civilized Humanity, the Unity of Indonesia, Democracy Guided by Inner Wisdom through Deliberation and Representation, and Social Justice for All Indonesian People. These values are reflected in the stages of pre-implementation, implementation, and post-implementation of the tradition, including collective prayers, mutual cooperation, deliberation, togetherness, and social solidarity. This study is expected to raise public awareness, particularly among the younger generation, of the importance of preserving local traditions as a medium for practicing Pancasila values and to serve as a reference for future research on character education based on local wisdom.